Changes in concentrations of hydrophilic organic contaminants and of endocrine-disrupting potential downstream of small communities located adjacent to headwaters - Jarosova, B; Blaha, L; Vrana, B; Randak, T; Grabic, R; Giesy, J P; Hilscherova, K (Environment international, 2012)
Endocrine-disruptive potential and concentrations of polar organic contaminants were measured in seven headwaters flowing through relatively unpolluted areas of the Czech Republic. Towns with Wastewater Treatment Plant (WWTP) discharges were the first known sources of anthropogenic pollution in the areas. River water was sampled several kilometers upstream (US) and several tens of meters downstream (DS) of the WWTP discharges, by use of Pesticide and Pharmaceutical Polar Organic Integrative Samplers (POCIS-Pest, POCIS-Pharm). Extracts of passive samplers were tested by use of a battery of in vitro bioassays to determine overall non-specific cytotoxicity, endocrine-disruptive (ED) potential and dioxin-like toxicity. The extracts were also used for quantification of polar organics. There was little toxicity to cells caused by most extracts of POCIS. Estrogenicity was detected in all types of samples even though US locations are considered to be background. At US locations, concentrations of estrogen equivalents (EEq) ranged from less than the detection limits (LOD) to 0.5 ng EEq/POCIS. Downstream concentrations of EEqs ranged from less than LOD to 4.8 ng EEq/POCIS. Concentrations of EEq in POCIS extracts from all DS locations were 1 to 14 times greater than those at US locations. Concentrations of EEq measured in extracts of POCIS-Pest and POCIS-Pharm were in a good agreement. Neither antiestrogenic nor anti/androgenic activities were detected. Concentrations of 2,3,7,8-TCDD equivalents (TEq(bio)) were detected in both types of POCIS at concentrations ranging from less than the LOD to 0.39 ng TEq(bio)/POCIS. Nearly all extracts of POCIS-Pharm contained greater concentrations of TEq(bio) activity than extracts of POCIS-Pest. Concentrations of pesticides and pharmaceuticals in extracts of POCIS were generally small at all sampling sites, but levels of some pharmaceuticals were significantly greater in both types of POCIS from DS locations. Chemical analyses along with the results of bioassays documented impacts of small towns with WWTPs on headwaters.
Keywords: endokrinní disruptory; biotest; Česká republika; chemické znečištění vody; Estrogens; sladká voda; monitorování životního prostředí; Water Pollution, Chemical; odpadní voda; Biological Assay; Dioxins; Waste Disposal, Fluid; Czech Republic; Environmental Monitoring; chemické látky znečišťující vodu; dioxiny; Pesticides; Fresh Water; hydrofobní a hydrofilní interakce; odpad tekutý - odstraňování; Wastewater; pesticidy; řeky; Hydrophobic and Hydrophilic Interactions; estrogeny; Water Pollutants, Chemical; Rivers; Endocrine Disruptors